Peran Guru Dalam Pengelolaan Kelas Berdasarkan Ibrani 10:24-25 di Paud Rehobot Seed Cikeas Bogor - Bey Todu; Sri Rezeki (Jurnal Silih Asah, 2024)
The role of the teacher in the management of the classroom, as reflected in Hebrews 10:24-25, was the primary foundation of education in the PAUD Rehobot Seed Cikeas Bogor. The role of the teacher is not only as the enforcer of learning, but also as the holder of social roles that influence student behavior. In this context, the teacher's role consists of a variety of actions that include assistance, encouragement, responsibility, and classroom management skills. As a class leader, the teacher is responsible for organizing a conducive learning process. They prepare teaching materials, organize classrooms, and use appropriate learning media to enhance students' skills. Not only that, teachers also act as motivators that encourage students to develop their potential. At PAUD Rehobot Seed Cikeas Bogor, the application of the teacher's role in classroom management has had a positive impact. Teachers pay attention to the obstacles that students face individually, give personal attention, and organize additional learning sessions after formal lessons. They use a variety of learning media, including visual audio, to enrich the student's learning experience. In addition, teachers also play an active role in advising and encouraging students to improve their learning performance.The overall role of this teacher is not only limited to the formal aspects of learning, but also includes a deep personal relationship with the student. This approach allows the teacher to strengthen moral values and facilitate the student's holistic development.Thus, the role of the teacher in the management of the classroom, inspired by the principles in Hebrews 10:24-25, not only optimizes the formal learning-teaching process, but also enriches personal interaction and values in education in PAUD Rehobot Seed Cikeas Bogor.